Russian Nomenclature of Human and Animals’ Interior Organs (an attempt of а reconstruction of а lexical group) - Ушинскене, Виктория (Slavistica Vilnensis, 2010)
In the last decades, the development of historical and comparative linguistics has been characterized by a special emphasis on lexics. Different lexical groups are being inspected in Slavonic linguistics as the subject of diachronic analysis. Unsufficiently investigated is the dialectic nomenclature dealing with the names of interior organs of living organisms. In this article a group of common names of interior organs was chosen as the subject of research. The sources of the investigation were: V. Dal’s Dictionary, Dictionary of Russian Dialects, regional Russian dictionaries, and some Old Russian texts. The following tasks were solved: to stratificate the material chronologically in order to establish its relative age; to discover the principles of nomination, and to investigate the possible directions of semantical transformations inside this lexical group. The results of this research show that the investigated terminology group is presented in anatomical terms of different chronological depth: of Indo-European, Proto-Slavonic, Eastern Slavonic and Russian origins. All of the words are polysemantic, only some lexemes correlate precisely with a certain organ. Most of them are of second meanings, and have formed as a result of semantic transformations of not only Slavonic names, but also of words borrowed from other languages. The latest terms reflect the stability and productivity of several ancient semantic models.